The effect of a short animated educational video on knowledge among glaucoma patients - Al Owaifeer AM (Dove Medical Press, 2018)
Adi Mohammed Al Owaifeer,1,2 Shaimaa Mohammed Alrefaie,3 Zainah Mohameddia Alsawah,3 Abdulaziz Ahmed Al Taisan,1 Ahmed Mousa,3 Sameer I Ahmad2,4,5 1Faculty of Ophthalmology, College of Medicine, King Faisal University, Al-Hasa, Saudi Arabia; 2King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 3Department of Ophthalmology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 4Department of Ophthalmology and Visual Sciences, University of Maryland School of Medicine, Baltimore, MD, USA; 5Glaucoma Consultants of Washington, Herndon, VA, USA Purpose: To evaluate the effectiveness of an educational video in increasing knowledge among glaucoma patients and to determine the factors that may influence a patient’s level of knowledge.Patients and methods: This was a pre–post intervention study on adult glaucoma patients attending the outpatient service at King Khaled Eye Specialist Hospital. The intervention tested was a short educational video that was edited specifically for this study. All patients completed a pre-video and post-video knowledge questionnaire; moreover, sociodemographic and clinical characteristics were obtained.Results: The total number of patients included was 196. The mean age of patients was 55.7±15.5 years. Overall, 55.1% were males, 29.6% were illiterate, 85.2% resided in an urban area, 62.8% had a low income, and 41.8% were unemployed. The mean pre-intervention knowledge score was 6 out of 17, and the post-intervention score was 11.1 (P≤0.001). Predictors of a poor knowledge score were old age (>60 years), female sex, illiteracy, rural residence, low income, unemployment, and a negative family history of glaucoma.Conclusion: The evaluated video intervention was effective in a short-term increase in knowledge among glaucoma patients. This tool may serve as an alternative to traditional educational methods. Keywords: glaucoma, education, questionnaire, video, animation